Sigma-Delta Modulators for Analog-to-Digital & Digital-to-Analog Conversion: A Review: Sigma-Delta Modulators for A/D and D/A Conversion: A Review - Ijaz, Khalid; Hussain, Zawar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Analog-to-digital and digital-to-analog converters manifest a very imperative role in many applications where data is interfaced with real analog world. The occurrence of some problems like jitter, quantization errors, integral nonlinearity and conversion time reduces the performance of both analog-to-digital (A/D) and digitalto-analog (D/A) converters. One of the most efficacious ways to combat these problems is the use of sigma-delta modulation. Sigma-delta modulators became very prominent due to their noise shaping characteristic in an analog-todigital and digital-to-analog conversion. A fundamental structure, noise shaping techniques and different architectures of sigma-delta modulators along with comparative analysis are discussed in this review paper.